The learning process of uniformity skills for novice rowers - Ushizu, A.; Kawahara, S.; Yamamoto, H. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
In the crew events which row with a number of rowers, it is thought that the important technical element is the uniformity of crew how well rowers can synchronize timing of movement oars (Wing AM & Woodburn C, 1995; A Baudouin & D Hawkins, 2004). The highly uniformity skills also could make up for the total low power in the crew. In case of instruction for novice rowers, due to enhancement of uniformity skills, they may be able to feel the sensation of propulsive force of boat. Therefore, it is thought that this sensation would affect their interests in rowing. The purpose of this study was to identify the learning process of uniformity skills for novice rowers, and to obtain the basic data to instruct for novice rowers.